Effect of different Organic Media on Cost Economics of Strawberry (Fragaria x ananassa Duch.) Propagated through Runners Raised on Beds under Protected Condition - Aaisha Nasim; G.D. Sahu; Jagdish Chawla; Ajay Singh; Mahabub Alam; Suhel Eraqui; Michi Tani; Gunja Thakur; Mohammad Faizan Husain; Shamsher Alam (Archives of Current Research International, 2024)
Impact of various Organic Media on Strawberry (Fragaria x ananassa Duch.) Cost Economics at the Precision Farming Development Centre (PFDC), during the year 2020-21, Department of Fruit Science, College of Agriculture, IGKV, Raipur (C.G.) using runners raised on beds under protected conditions. Eight treatments and three replications made up the completely randomised design (CRD) used for the experiment’s layout. The combination of cocopeat, rice husk, and vermicompost (1:1:1) was found to be the most efficient among the different treatments in terms of economy. In terms of economical aspects maximum gross return (7844165 Rs./ha), maximum net return (5983079 Rs./ha) and highest Benefit: Cost ratio recorded (3.22:1).